A Pragmatic Analysis of Flouting Maxims in Classroom Verbal Interaction as Seen in Freedom Writers Movie - Fidelis Elleny Averina (Surakarta English and Literature Journal, 2023)
Successful classroom verbal interactions will occur when both the teacher and the students intend to be cooperative conversational agents contributing to the conversation's aims. In Pragmatics, this underlying principle is called Grice’s conversational maxims. However, in the classroom, both sides often intentionally flout these conversational maxims. Thus, this research aimed to conduct a pragmatic analysis to investigate the types of Grice’s conversational maxims violated by the main character of Freedom Writers movie along with the categories of teacher’s verbal interactions found in that movie under Flanders Interaction Analysis Categories System (FIACS). Using the document analysis method, the researcher used the movie transcript as the primary document to be analyzed. The findings showed that the four maxims were violated intentionally for several reasons, including warning the students of the consequences of their actions, encouraging them, avoiding certain topics of discussion, and emphasizing important messages without blatantly stating them to the whole class, and avoiding hurting the students’ feelings. Meanwhile, under Flanders Interaction Analysis Categories (FIAC), direct and indirect talks could be found in the movie. The result of this study can provide educators and pre-service teachers a glimpse of the importance of promoting appropriate classroom verbal interactions by analyzing the quality of classroom verbal interaction in terms of Grice’s Conversational Maxims and Flanders’ Interaction Analysis.